Apache Kafka quick start guide : leverage Apache Kafka 2.0 to simplify real-time data processing for distributed applications /: leverage Apache Kafka 2.0 to simplify real-time data processing for distributed applications. ([2018]) - Estrada, Raúl
No abstract available